Effects of ammoniation on the quality of tropical grass hays - Reis, Ricardo Andrade; Garcia, Rasmo; Queiroz, Augusto César de; Silva, Dirceu Jorge da; Ferreira, Joel Queiroga (Pesquisa Agropecuaria Brasileira, 1991)
Molassesgrass (Melinis minutiflora Beauv.) and Brachiaria decumbens Stapf (signalgrass) harvested in the post-flowering period were treated with 0, 2, 4 and 6% anhydrous ammonia for 30 or 45 days and thereafter subjected to aeration for 0, 15, 30, 45 and 60 days to study their quality. No effects (P > 0.05) of treatment periods on chemical composition and digestibility of the hays were observed. Ammoniation did not alter (P > 0.05) ADF, cellulose or lignin levels but caused a decrease (P < 0.05) in NDF and hemicellulose levels. Total nitrogen (TN), acid detergent insoluble nitrogen (ADIN) and in vitro dry matter digestibility (IVDMD) increased (P < 0.05) with ammoniation. Total nitrogen (TN) levels and digestibility diminished (P < 0.05) in response to aeration during storage from 0 to 60 days.
Keywords: ammonia levels; treatment periods; aeration periods